PEMBERDAYAAN PETERNAK AYAM RAS PEDAGING SISTEM KEMITRAANDENGAN PENGUATAN KOMITMEN KERJASAMA INTI-PLASMA - Cokorda Bagus Dharma Putra Mahardika (Politeknik Pertanian Negeri Kupang, 2018)
Broiler agribusiness is currently leading to consolidation of farmers and broiler industries with a contract farming partnership. The broiler industry that implements cooperation between plasma/farmers and the nucleus/large integrators has yet improve the welfare of small-scalefarmers. In fact, farmers are more accepting risks than getting profits and so that it is not accordance with the principles of partnership and empowerment. Basically, farmers need the commitment of stakeholders to support their empowerment. The method to encourage strengthening ofstakeholder’scommitments starting from: (a) The Government or stakeholders initiating meetings between farmers and local integrator to discuss evaluating the implementation of contract farmingpartnership; (b) The government monitors the local integrators to make a fair cooperation contract or memorandum of understanding; (c) Periodic monitoring of contract farming partnership agreements, such as procurement of inputs, management and outputs; (d) Implementing integrated assistance where stakeholders are involved.